2013
DOI: 10.4021/cr279e
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization of Patients With Acute Coronary Syndrome in Germany

Abstract: BackgroundThe aim of this study was to determine the health care utilization of patients with acute coronary syndrome (ACS) of one German statutory health insurance. The utilization of ambulatory services as well as of inpatient rehabilitation should be regarded. Moreover, the study should reveal the prescription of drugs for secondary prevention. Here, patients showing guideline corresponding prescriptions should be compared with patients without such prescriptions.MethodsA retrospective claims data analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Despite guideline recommendations, studies found suboptimal APT utilisation. [5][6][7] However, information on the extent of APT use at different treatment stages, and the role of particular individual characteristics, is very limited. Policy makers and providers would benefit from a detailed understanding of APT use at different treatment stages to inform development of quality-improvement interventions and policies.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…Despite guideline recommendations, studies found suboptimal APT utilisation. [5][6][7] However, information on the extent of APT use at different treatment stages, and the role of particular individual characteristics, is very limited. Policy makers and providers would benefit from a detailed understanding of APT use at different treatment stages to inform development of quality-improvement interventions and policies.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%